2012
DOI: 10.1038/nchembio.764
|View full text |Cite
|
Sign up to set email alerts
|

Timing facilitated site transfer of an enzyme on DNA

Abstract: Many enzymes that react with specific sites in DNA exhibit the property of facilitated diffusion, where the DNA chain is used as a conduit to accelerate site location. Despite the importance of such mechanisms in gene regulation and DNA repair, there have been few viable approaches to elucidate the microscopic process of facilitated diffusion. Here we describe a new method where a small molecule trap (uracil) is used to clock a DNA repair enzyme as it hops and slides between damaged sites in DNA. The “molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
249
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(261 citation statements)
references
References 45 publications
12
249
0
Order By: Relevance
“…This apparent paradox for the passive mechanism can be resolved if the polymeric nature of DNA is considered along with the microscopic dynamic translocation behavior of these enzymes when interacting with specific and nonspecific DNA chains 34,35 In this regard, the macroscopic off rate from a site is determined by the rate of irreversible departure of the enzyme from the site, defined as its equilibration with all other substrate or product molecules in bulk solution. For an enzyme that interacts with DNA, the macroscopic rate also contains the rapid microscopic excursions that an enzyme makes away from a specific site before it irreversibly departs.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent paradox for the passive mechanism can be resolved if the polymeric nature of DNA is considered along with the microscopic dynamic translocation behavior of these enzymes when interacting with specific and nonspecific DNA chains 34,35 In this regard, the macroscopic off rate from a site is determined by the rate of irreversible departure of the enzyme from the site, defined as its equilibration with all other substrate or product molecules in bulk solution. For an enzyme that interacts with DNA, the macroscopic rate also contains the rapid microscopic excursions that an enzyme makes away from a specific site before it irreversibly departs.…”
Section: Discussionmentioning
confidence: 99%
“…The opening times for more stable, undamaged/matched DNA are expected to be much longer than for mismatch DNA (55). Although the 1D diffusion constants of Rad4/XPC on DNA are yet to be reported, studies have revealed microsecond-regime residence times per DNA site for a wide range of DNA-binding proteins (7)(8)(9)(10)(11)(12)(13). Thus, the observed opening time of Rad4 is many orders of magnitude longer than the typical residence times per DNA site.…”
Section: Significancementioning
confidence: 99%
“…How DNA-binding proteins search for and identify their target sites embedded in a vast excess of nontarget sites, especially if using only thermal energy, is a fundamental question in biology. Several lines of evidence indicate that proteins use some combination of 3D diffusion in the bulk solution and 1D diffusion while nonspecifically bound to DNA, and use this "facilitated diffusion" as a means to search efficiently in genomic DNA for their targets (1)(2)(3)(4)(5)(6)(7). Direct observations of proteins diffusing on nonspecific DNA have revealed residence times per base pair site ranging from 50 ns to 300 μs (7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…lyzed excision of uracil (1,2) and oxidized bases such as 8-oxoG (3,4); mismatch repair proteins working in concert to remove DNA polymerase-catalyzed misincorporated bases and looped out structures resulting from short insertions and deletions (6,7); and endonucleases that catalyze the cleavage of dsDNA at restriction motifs (5,12). In contrast, enzymes that act on ssDNA have been investigated to a far lesser extent.…”
mentioning
confidence: 99%